[tex]\lim_{x \rightarrow 0}\frac{\sqrt[3]{x+1}\sqrt{2x^2+x+1}-1}{x}\\=\lim_{x \rightarrow 0}\frac{(\sqrt[3]{x+1}-1)\sqrt{2x^2+x+1}+\sqrt{2x^2+x+1}-1}{x}\\=\lim_{x \rightarrow 0}\frac{\frac{x+1-1}{\sqrt[3]{(x+1)^2}+\sqrt[3]{x+1}+1}\sqrt{2x^2+x+1}+\frac{2x^2+x+1-1}{\sqrt{2x^2+x+1}+1}}{x}\\=\lim_{x \rightarrow 0}x.\frac{\frac{1}{\sqrt[3]{(x+1)^2}+\sqrt[3]{x+1}+1}\sqrt{2x^2+x+1}+\frac{2x+1}{\sqrt{2x^2+x+1}+1}}{x}\\=\lim_{x \rightarrow 0}\frac{1}{\sqrt[3]{(x+1)^2}+\sqrt[3]{x+1}+1}\sqrt{2x^2+x+1}+\frac{2x+1}{\sqrt{2x^2+x+1}+1}\\=\frac{1}{3}.1+\frac{1}{2}=\frac{5}{6}[/tex]